2006
DOI: 10.3390/11121009
|View full text |Cite
|
Sign up to set email alerts
|

A New Neolignan Glycoside from the Leaves of Acer truncatum

Abstract: Abstract:A new neolignan glycoside, (7R,8R)-7,8-dihydro-9′-hydroxyl-3′-methoxyl-8-hydroxymethyl-7-(4-hydroxy-3-methoxyphenyl)-1′-benzofuranpropanol 9′-O-β-Dglucopyranoside (1) was isolated from the leaves of Acer truncatum along with (7), chlorogenic acid (8) and neochlorogenic acid (9). Their structures were elucidated on the basis of extensive spectroscopic data. The absolute configuration of compounds 1 was established by its CD spectrum. The antibacterial activities of compounds 1-7 were evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…These results indicated that 1 had two phenylpropanoid units. 16,17) Significant HMBC correlations were also observed between H-7/C-5′ and H-8/C-4′. Therefore, it could be concluded that two phenylpropanoids formed a 7,8-dihydro-8-hydroxymethyl-7-phenyl-1′-benzofuranpropanol skeleton.…”
Section: 4-dihydroxyphenylethyl Alcohol 8-o-β-d-glucopyranosidementioning
confidence: 75%
See 4 more Smart Citations
“…These results indicated that 1 had two phenylpropanoid units. 16,17) Significant HMBC correlations were also observed between H-7/C-5′ and H-8/C-4′. Therefore, it could be concluded that two phenylpropanoids formed a 7,8-dihydro-8-hydroxymethyl-7-phenyl-1′-benzofuranpropanol skeleton.…”
Section: 4-dihydroxyphenylethyl Alcohol 8-o-β-d-glucopyranosidementioning
confidence: 75%
“…17,18) Accordingly, the structure of 1 was identified as (7S,8S)-7,8-dihydro-8-hydroxymethyl-7-(4-hydroxy-3-methoxyphenyl)-1′-benzofuranpropanol 2′-O-β-D-glucopyranoside, named akeqintoside A, as drawn in Fig. 1 14) The…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations